Primates in Print: Popularizing Interspecies Kinship in Huxley’s ’Evidence as to Man’s Place in Nature’ - Pasquini, Robert (Pivot: A Journal of Interdisciplinary Studies and Thought, 2016)
This paper examines the bibliographic features of Thomas H. Huxley’s 1863 work Evidence as to Man’s Place in Nature in order to focalize Huxley’s public engagement with non-professional audiences and consumerist market forces. Huxley’s shaping of Victorian scientific practices and his cultural contributions to natural history have been thoroughly documented, yet the hermeneutic potential of the popular work’s bibliographic and visual elements has not been adequately addressed. When amalgamated through a re-conceived process of reading, the textual and visual features of Evidence materialize the evidence of evolutionary processes to which humans themselves are subject to. After confronting humans and primates in print, Huxley’s audience understood that the socio-cultural barriers to the dismantling of animal/human dichotomies imposed by humanist ideology were made available to rational critique. Because of its wide-ranging success as a catalyst of public—not just professional—acknowledgment of evolution, I contend that Evidence’s physical and visual features should not be overlooked as major contributing factors in the dissemination and acceptance of natural explanation. This research engages with pressing questions concerning the interclass popularization of Victorian science: how did tactile decisions about the object fashion its own reception? Can evolution be presented via visual rather than purely conceptual means? How immersed was Huxley’s product in burgeoning capitalistic forces? Ultimately, understanding Evidence’s status as a marketable visual product sheds light on how Victorians (professional and colloquial subjects alike) propagated, absorbed, and contemplated the ramifications of evolution.